The Impact of Institutional Support, Lecturer Capabilities, and Product Development on the Commercialization of Health Research - Ratih Gantini Nurhayati; Ria Arifianti; Dian Fordian (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The commercialization of university research in the health sector is a strategic pathway for transforming academic knowledge into societal and economic value. Universitas Padjadjaran has generated numerous health-related innovations, yet its progression toward full downstream application and market entry remains uneven. This study examines the influence of institutional support, lecturer capability, and product development readiness on the success of research commercialization among academics in the health cluster. A qualitative design combining surveys and interviews was conducted from September to October 2025, involving 114 respondents selected purposively from 282 lecturers with research-based products. The findings show that commercialization success is strongly shaped by four key factors: sustained institutional support and incentive policies, collaborative networks with industry and government, lecturers’ competencies in innovation management, and research effectiveness aligned with market and regulatory requirements. These results highlight the importance of strengthening institutional ecosystems to support research downstreaming and provide practical guidance for policymakers and university leaders in fostering sustainable academic entrepreneurship in Indonesia.